Synthesis, characterization and evaluation of immunomodulatory, anticancer, antibacterial and wound healing activities of alginate nanoparticles loaded with heterotrigona itama honey - Alhatamleh, Mohammad Ahmed Issa (2023)
This research aimed to fabricate alginate nanoparticles (ALG-NPs) loaded with stingless bee honey (SBH), and to assess the ability of the honey-loaded ALG-NPs (HALG- NPs) to modulate immune responses, suppress cancer proliferation and migration, accelerate wound healing and inhibit bacterial growth compared to crude SBH and free ALG-NPs. The major components of honey and its physicochemical and antioxidant properties were analyzed. The H-ALG-NPs were fabricated by an ioniccross- linking technique. The size and charge of the H-ALG-NPs were determined by dynamic light scattering, and they were characterized using TEM, SEM, FTIR, XRD, DSC and TGA. The DPPH radical scavenging activity, encapsulation efficiency (EE) and loading capacity (LC) of the H-ALG-NPs were also determined. The cytotoxicity and anti-migration activity of the H-ALG-NPs were in vitro tested against A549 lung cancer, MCF-7 breast cancer, MDA-MB-231 breast cancer, U87 glioblastoma and normal dermal fibroblast cell lines. The effects of the H-ALG-NPs on the mRNA expressions of TNF-α, IL-10, IL-6, IL-1β, IL-8 and IRAK1 genes in these cell lines were measured by qPCR. The mRNA expressions of these genes along with TGF-β, TLR4, IRAK1, FOXP3, TFRC, PGE2, IDO1, CD73, CD39, COX1 and COX2 genes were also measured in THP-1 differentiated macrophages treated with the H-ALGNPs. The wound-healing activity of the H-ALG-NPs was evaluated in a mouse model, while their antibacterial activity was evaluated against Escherichia coli, Klebsiella pneumonia, Staphylococcus aureus and Bacillus cereus by the MIC method. The properties of honey were consistent with the IHC-Codex and Malaysian standards, and it had good antioxidant activity. The spherical H-ALG-NPs had a size of 312 ± 4.32 nm and -21.2 ± 0.29 mV surface charge. The FTIR, XRD, DSC and TGA confirmed honey loading within the ALG-NPs. The H-ALG-NPs had a high EE of 84.74% ± 1.42 with an LC of 23.12% ± 0.26, while the IC50 of DPPH was significantly higher than crude SBH (p > 0.00001). The MTT assay showed significantly higher toxicity against cancer cell lines by the H-ALG-NPs compared to honey, and vice versa for fibroblasts (p ≤ 0.001). The scratch assay showed significantly higher anti-migration activity by the H-ALG-NPs against A549 (p ≤ 0.001), MCF-7 and MDA-MB-231 (p ≤ 0.0001) cancer cells compared to honey. The expressions of several inflammatory and inflammatory-related genes in cancer cell lines (i.e., MCF-7, MDA-MB-21, A549 and U87), fibroblasts and THP-1 macrophages were significantly modulated upon treatment with the H-ALG-NPs compared to honey. Importantly, the findings suggest that the H-ALG-NPs, but not crude honey, may tend to reduce the output of proinflammatory signals, promotes the release of anti-inflammatory signals, and activates M2 macrophages. Wounds treated with the H-ALG-NPs showed superior healing activity than crude honey. The H-ALG-NPs exhibited 4-fold stronger antibacterial activities than crude honey against the Gram-positive and Gram-negative bacteria. In conclusion, the results suggested that the H-ALG-NPs have enhanced antioxidant, immunomodulatory, anticancer, antibacterial and wound healing activities. This study indicates that the H-ALG-NPs can be fabricated simply by a cost-effective technique with promising therapeutic properties.